2022
DOI: 10.1177/02601060221099782
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate fruits and vegetables consumption among Malaysian adults during the COVID-19 pandemic

Abstract: Background: The COVID-19 pandemic has negatively impacted the eating behaviours of people especially fruits and vegetable intake. No study has addressed the fruits and vegetables intake during the COVID-19 in Malaysia. Aim: to assess the daily intake of fruits and vegetables among Malaysian adults during the COVID-19 outbreak, perceived changes in intake, as well as factors associated with the changes in intake. Methods: A cross-sectional study was conducted through online platforms and a total of 506 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
1
2
0
1
Order By: Relevance
“…Our finding showed a higher sugar consumption than a local study that showed mean sugar intake from SSB among public Malaysian university students was 30.90 g of sugar (6 teaspoons) of sugar per day (Hamirudin et al, 2018). This result is in line with other studies, which found that university students had poor dietary habits, including a low fruits and vegetables consumption and a higher consumption of SSB (Bawadi et al, 2019;Lo et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Our finding showed a higher sugar consumption than a local study that showed mean sugar intake from SSB among public Malaysian university students was 30.90 g of sugar (6 teaspoons) of sugar per day (Hamirudin et al, 2018). This result is in line with other studies, which found that university students had poor dietary habits, including a low fruits and vegetables consumption and a higher consumption of SSB (Bawadi et al, 2019;Lo et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…It also indicated that fruits such as bananas, papaya, mango, orange, and pineapple and vegetables like beans, dhal, carrot, potato, leeks, pumpkin, Gotukola and Mukunuwenna were the most frequently consumed by the respondents. A survey conducted by Lo et al (2022) also proved the same thing, where the result is discouraging since the majority of the respondents have less knowledge about the consumption of vegetables and fruits per day as recommended by the WHO. This study found that the average amount of fruits and vegetables consumed daily by Malaysian adults in this study was less than one serving compared to the recommended intake of five servings.…”
Section: Past Studies Of Fruits and Vegetables Consumption Patternmentioning
confidence: 81%
“…Besides, emotional eating associated with higher levels of stress and anxiety could lead to excessive intake of comfort food containing high amount of sugar and fat ( Husain and Ashkanani, 2020 ). Furthermore, Malaysian adults reported an increased consumption of sugar-sweetened beverages ( Cheng and Lau, 2022 ) and decreased intake of fruits and vegetables ( Lo et al, 2022 ) during COVID-19. These findings suggest that stress, depression, and anxiety can synergistically cause adverse effects on body weight during the pandemic due to poor dietary choices.…”
Section: Discussionmentioning
confidence: 99%